Potentially toxic elements in wild Agassiz’s desert tortoises: tissue concentrations and association with disease - Berry, Kristin H.; Christopher, Mary M.; Jacobson, Elliott R. (Frontiers in Veterinary Science, 2024)
BackgroundDesert tortoise (Gopherus agassizii) populations have continued to decline due to infectious and other diseases, predation, and habitat alteration. The potential contribution of minerals and heavy metals to tortoise health and susceptibility to disease remains uncertain.ObjectiveThe objective of this study was to evaluate the results of elemental analysis on trace minerals, macrominerals, and heavy metals in scute keratin, kidney, and liver from ill and dying desert tortoises salvaged for necropsy between 1993 and 2000.MethodsSalvaged tortoises were categorized by size (adult, juvenile), geographic location, and primary disease based on necropsy findings. A subset of tortoises that were injured or killed by vehicular trauma or predation but with no notable pathologic abnormalities was used for comparison with diseased tortoises. The panel of elements was analyzed in scute keratin, kidney, and liver samples by inductively-coupled plasma spectrometry and atomic absorption spectrophotometry.ResultsNecropsies were done on 46 tortoises, including 9 juveniles, salvaged from 5 regions in the Colorado and Mojave Deserts of California. Primary diseases were cutaneous dyskeratosis (n = 9), infection/inflammation (n = 8), malnutrition (n = 7), mycoplasmosis (n = 5), and urolithiasis (n = 3); 14 tortoises died of trauma. Concentrations of elements differed by tissue, size, desert region, and disease status (p < 0.05). Tortoises with cutaneous dyskeratosis had higher Se concentrations, primarily in keratin and liver, than tortoises with other diseases (p < 0.001). Juveniles were more likely than adults to have high Pb, Sn, and Zn levels (p < 0.05). All tortoises had detectable levels of more than one potentially toxic heavy metal, including As, Cd, Cr, Hg, Ni, Pb, Sn, and V.ConclusionPotentially toxic elements are frequently found in tissues from tortoises in desert regions of California, with higher concentrations in diseased tortoises. Metal exposure from soils, mining, historic and ongoing military activities, and other human activities could increase susceptibility to disease in desert tortoises.